Hormonal Contraception in Perimenopause: What to Consider to Guide the Choice - Fidecicchi, Tiziana; Caretto, Marta; Chen, Giulia; Simi, Davide; Montt Guevara, Maria M.; Giannini, Andrea; Luisi, Stefano; Simoncini, Tommaso (Seminars in Reproductive Medicine, 2025)
Perimenopausal women have specific needs when it comes to contraception. Although fertility rates generally decrease after age 40, pregnancy is still possible and may be associated with a higher risk of obstetric and fetal complications. Moreover, women may experience bothersome symptoms during perimenopause due to anovulatory cycles and fluctuating estrogen levels, such as abnormal uterine bleeding, vasomotor symptoms, migraines, and mood disorders. Additionally, age increases the risk of the most common side effects of well-known contraceptives, particularly those containing estrogen. For this reason, contraception counseling during perimenopause should be tailored to the woman's characteristics. It should include three steps: evaluating the woman's needs and symptoms; evaluating the potential benefits of the chosen method; evaluating risk factors that may contraindicate certain choices. No contraceptive method is contraindicated solely based on age. Among combined hormonal contraceptives, if no contraindication exists, natural estrogens should be preferred after 40 years old. On the other hand, progestin-only methods can also be safely used in the presence of cardiovascular risk factors. This review will address the main reasons why a woman may need an HC method and how to make a tailored and informed choice.
Keywords: menopause transition; vasomotor symptoms; hormonal contraception; combined oral contraceptives; long-acting reversible contraceptives